2011
DOI: 10.1103/physrevlett.106.056601
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Contributions to the Spin Hall Effect of Alloys

Abstract: A fully relativistic description of the spin-orbit induced spin Hall effect is presented that is based on Kubo's linear response formalism. Using an appropriate operator for the spin-current density a KuboStředa-like equation for the spin Hall conductivity (SHC) is obtained. An implementation using the Korringa-Kohn-Rostoker band structure method in combination with the coherent potential approximation allow detailed investigations on various alloy systems. A decomposition of the SHC into intrinsic and extrins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
151
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 32 publications
7
151
0
Order By: Relevance
“…And the calculated SHCs 32,33 are found to agree well with the corresponding experimental values in many metals such as Al 35 , Pt 36,37 , Au and Pd 38 , suggesting that the intrinsic SHE is dominant in the high resistivity regime in pure metals. Nonetheless, recent experimental 39,40 and theoretical [41][42][43][44][45] studies showed that certain impurities could also give rise to large SHE in impure metals. However, the SHE in ferromagnets remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…And the calculated SHCs 32,33 are found to agree well with the corresponding experimental values in many metals such as Al 35 , Pt 36,37 , Au and Pd 38 , suggesting that the intrinsic SHE is dominant in the high resistivity regime in pure metals. Nonetheless, recent experimental 39,40 and theoretical [41][42][43][44][45] studies showed that certain impurities could also give rise to large SHE in impure metals. However, the SHE in ferromagnets remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the fact that the SHE has been successfully observed in various types of experiments [7][8][9], it is expected that the spin Nernst effect would also be detectable. However, limitations on the magnitude of temperature gradients in metals can diminish the magnitude of the spin Nernst currents [10].Ab-initio studies [11][12][13][14] and experiments [15] suggest that the extrinsic SHE induced by the skew-scattering off impurities can be large due to a large difference in the spin-orbit coupling strength of the impurities and the host. However, this argument is not applicable to the SNE, because the thermal transport coefficients entering the expression for the spin Nernst conductivity (SNC) are determined to a first approximation by the derivative of the conductivities around the Fermi energy (E F ), and not by the their values directly at it.…”
mentioning
confidence: 99%
“…It is therefore indicated that the SHC and spin Hall angle in the NM layer can be tuned significantly via the SOC strength. As one of major issues in this field [17][18][19][20][21][22] , the mechanism of the extrinsic SHC needs further investigations.…”
Section: (E)mentioning
confidence: 99%
“…The measured SHC should in principle consist of the intrinsic and extrinsic terms for x in the region from 0 to 1.0. The extrinsic one, caused by the asymmetric scattering at impurity sites is expected to be negligible near the ending data points 18,43 and to become prominent near x = 0.5. Clearly, for the present PdPt alloys, the intrinsic term plays a dominant role in the measured SHC and the extrinsic term can be neglected, as observed in Ir doped Pt 18 .…”
Section: (E)mentioning
confidence: 99%
See 1 more Smart Citation